Effect of organic amendments on rice yield trend, phosphorus use efficiency, uptake, and apparent balance in soil under long-term rice-wheat rotation. (28th May 2017) - Mitran, Tarik; Mani, P. K.
ABSTRACT: The experiment was conducted in a 22nd cycle of rice-wheat rotation established in the eastern India with a randomized block designed with various combinations of inorganic and organic sources of nutrients like farm yard manure (FYM), paddy straw (PS), and green manure in rice crop only. Application of nitrogen, phosphorus, and potassium (NPK) and its combination with FYM, PS, and green manuring increased the grain yield of rice significantly. Rice yield declined only in control plots (−0.003 t ha −1 year −1 ), whereas positive yield trend was maintained in all the treatments. All organically amended plots showed a better uptake as well as use efficiencies of applied phosphorus (P) inputs over control. The apparent P balance showed positive value in control treatment over the years ranging from −4.8 to 24.8 kg ha −1 year −1 . The positive yield trend of rice was maintained due to buildup of P from various organic inputs.